Staying In: The Study of Pacific Islanders in College Football Using Indigenous Methodologies (Asian Journal of Social Science Studies, 2017)
This is a qualitative study that investigates how culture and race impact the college experiences of PI football players, how those experiences enhance or inhibit their persistence in higher education, and to introduce Pacific Islander Cultural Racism Theory (PI-CRiT) as a guiding framework for the research. The methodology for this study weaves three Pacific Islander cultural constructs together to ensure that the research process is respectful of each participant, their community, and their gift of mo‘olelo (story). This PI methodology disrupts dominant research paradigms by suggesting that data collection, analysis and interpretation should align with its participants’ ontology, epistemology and axiology. That is, the methods to gain more knowledge about reality (methodology), should align with the participants’ views about reality (ontology), their ways of thinking about reality (epistemology), and their ethics, morals and values that guide their interaction in that reality (axiology).